Information and communications technology (ICT) and airspace management in Nigeria: An analysis (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study explores the pivotal role of Information and Communications Technology (ICT) in managing Nigeria's airspace, focusing on both civil aviation and defense sectors. Utilizing a descriptive survey method and qualitative data analysis, the research adopts the Routine Activity Theory by Cohen and Felson (1979) as its theoretical framework. The findings highlight that inadequate monitoring and policing of airspace infrastructure have exposed Nigeria to criminal and subversive activities, threatening national security. To address this, the study recommends establishing a multi-stakeholder governance system. This system should integrate various private, public, andinternational authorities within the ICT sector, under the oversight of the Nigerian Information Technology Development Agency (NITDA). Comprising technocrats skilled in airspace-related criminality, such as cybercrimes, cyber terrorism, and cyber espionage, this regime would be tasked with monitoring, protecting, and securing Nigeria's airspace infrastructure.
Keywords: Information and Communication Technology (ICT); Airspace Management; Threats; National Security; Defence Management